Modern equity: At the edge of formal reasoning? - YIP, Man (Institutional Knowledge at Singapore Management University, 2019)
Equity, in its inception, was more inclined than the common law towards substantive reasoning – with reference to conscience, moral reasons and circumstances of the case. Ecclesiastical Chancellors did not consider themselves bound by precedents. These features of early equity may be explained by its historical function to supplement common law and mitigate its harshness. The concern was with ensuring that justice was achieved in each case, particularly where the dispute could not be adequately dealt with by common law. Equity nevertheless progressively retreated towards formal reasoning – characterised by rules, fixed criteria and strict application of stare decisis principles – in conformity with the English vision of ‘law’.